2010
DOI: 10.1021/op100102m
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Microwave-Mediated Drying Process of Thermally Unstable / Labile Products

Abstract: The drying behavior of (S)-N-acetylindoline-2-carboxylic acid, precipitated (1a, 17 wt %) and nonprecipitated (1b, 5 wt %), and N-acetyl-(S)-phenylalanine ((S)-2-acetamido-3-phenylpropanoic acid, 2), both pharmaceutical intermediates, and of cocarboxylase hydrochloride (thiamine pyrophosphate, 3), a coenzyme, a bioactive form of vitamin B 1 , being a thermolabile substance, has been determined in straightforward drying setups. The method of supplying energy to the system had a profound influence on the drying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
1
0
0
1
Order By: Relevance
“…Thus, the energy efficiency factor calculated as the ratio Q dehydration /Q exp is 0.23, which is in a good accordance with our previous results obtained in the investigations of MW-assisted drug substances drying and phosphoric acid dehydration [27,28], wherein the same MW installation was used. Thus, it may be concluded that high factors of MW irradiation utilization can hardly be achieved at a laboratory scale.…”
Section: Energy Estimations and Process Scale-upsupporting
confidence: 90%
“…Thus, the energy efficiency factor calculated as the ratio Q dehydration /Q exp is 0.23, which is in a good accordance with our previous results obtained in the investigations of MW-assisted drug substances drying and phosphoric acid dehydration [27,28], wherein the same MW installation was used. Thus, it may be concluded that high factors of MW irradiation utilization can hardly be achieved at a laboratory scale.…”
Section: Energy Estimations and Process Scale-upsupporting
confidence: 90%
“…Для сравнения параметров термического синтеза с микроволновым процессом параметры последнего были рассчитаны, исходя из теплофизических расчетов, определения диэлектрических характеристик веществ (см. далее по тексту) и с учетом эффективности использования микроволнового излучения [18], а также исходя из предположения, что номинальная мощность микроволнового источника соответствует мощности электрического обогревателя в термических экспериментах (5 кВт).…”
Section: масштабирование процесса фосфорилирования тиаминхлоридаunclassified